Malting and fermentation effects on antinutritional components and functional characteristics of sorghum flour. Issue 1 (12th November 2017) - Ojha, Pravin; Adhikari, Roshan; Karki, Roman; Mishra, Achyut; Subedi, Ujjwol; Karki, Tika Bahadur
Abstract: The research was aimed to observe the effect of malting and fermentation on antinutritional component and functional characteristics of sorghum flour. For whole sorghum flour, cleaned sorghum grain was milled to pass through 40 mesh sieve. For malting, cleaned sorghum grain was steeped in 0.2% calcium hydroxide solution for 24 hr and then germinated for 48 hr at 90% RH and 27 ± 2°C. Sprout was removed, dried in hot air oven at 50 ± 2°C for 24 hr and milled to pass through 40 mesh sieve. For fermented sorghum flour, 13.3 mg% diastase and 2 mg % pepsin (on the basis of whole sorghum flour weight) was added to cooked (88 ± 2°C) sorghum flour and left for 1 hr. Lactobacillus plantarum (10 7  cfu/g) was inoculated and incubated at temperature 30 ± 2°C for 48 hr. The fermented slurry was dried at 50 ± 2°C in hot air oven for 24 hr and milled to pass through 40 mesh sieve. The lower yield of sorghum flour was obtained compared to whole and malted sorghum flour. Germination of sorghum reduced phytate, tannin, and oxalate by 40%, 16.12% and 49.1%, respectively, whereas fermentation of sorghum flour reduced above by 77%, 96.7% and 67.85%, respectively. There was no significant change in hydrogen cyanide in malted sorghum flour compared to whole sorghum flour, but fermentation of sorghum flour reduced hydrogen cyanide by 52.3%. Bulk density and viscosity was significantly reduced by the malting and fermentation, whereas water absorption capacity and oil absorption capacity was markedly increased by the malting and fermentation. Fermented flour was good due to reduced ANF and improved functional property despite of lower yield. Abstract : The research aimed to study the effect of malting and fermentation on antinutritional factors (ANF) and functional property of sorghum flour. Fermented flour was good due to reduced ANF and improved functional property despite of lower yield.